The Complexity of Human Experiences: A Study of William Faulkner’s Rendering of Time and Memory in The Sound and the Fury (مجلة ديالى للبحوث الانسانية, 2022)
William Faulkner unfolds an unconventional rendering of time and memory in his novels for he was highly influenced by two of the most famous writers of the age, i.e., the French philosopher and thinker, Henri Bergson and the novelist James Joyce, in their perspectives concerning time, memory and human life. Faulkner attempts to reveal how time is continuous and cannot be stopped like a flowing stream, and that time is measured only by the human memories of the past. To him, time is not orderly and it does not follow a linear or chronological pattern. He argues instead that time is fluid and malleable and that it is measured by human experiences and not by the mechanical ticking of a clock.